Levels of Inflammatory Cytokines IL-1β, IL-6, IL-8, IL-17A, and TNF-α in Aqueous Humour of Patients with Diabetic Retinopathy. (4th April 2018) - Feng, Songfu; Yu, Honghua; Yu, Ying; Geng, Yu; Li, Dongli; Yang, Chun; Lv, Qingjun; Lu, Li; Liu, Ting; Li, Guodong; Yuan, Ling
Abstract : Diabetic retinopathy is the leading cause of blindness in working age individuals in developed countries. However, the role of inflammation in the pathogenesis of DR is not completely understood. This is an observational clinical research enrolling 80 type II diabetic patients who had undergone cataract surgeries either with DR or without DR. All cases were further categorized by the proliferative stages of retinal neovascularization and by the lengths of diabetic history. The levels of inflammatory cytokines including IL-1 β, IL-6, IL-8, IL-17, and TNF- α in aqueous humour were tested. Results in this study indicated that these cytokine levels were increased in DR patients and might have a synergistic effect on the pathogenesis of this disease. They were also elevated along with the progression of neovascularization, reflecting the severity of DR. The results also suggested that for diabetic patients, the higher these levels are, the sooner retinal complications might appear. In conclusion, the levels of inflammatory cytokines IL-1 β, IL-6, IL-8, IL-17A, and TNF- α in aqueous humour may be associated with the pathogenesis, severity, and prognosis of DR.